Analysis Influence Of Total Quality Management On Competitive Advantages With Technological Innovation And Knowledge Management As Moderating Variables - Chairunnisa Chairunnisa; Muhammad Tojibussabirin; Syaiful Iqbal (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to analyse the effect of total quality management on competitive advantage at PT Bank Pembangunan Dearah Tbk. with technological innovation and knowledge management as moderating variables. Methodology/approach: Primary data were collected from 373 Bank Jatim employees through questionnaire distribution. Data were analysed using Partial Least Square (PLS) statistical technique to test the relationship between variables. Findings: Total quality management is proven to be a factor that can affect competitive advantage. Technological innovation is able to strengthen the influence of total quality management on competitive advantage, but knowledge management is unable to strengthen or weaken the influence of total quality management on competitive advantage. Practical implications: This research is expected to be a consideration for the management of banking companies in integrating technological innovation and knowledge management through the application of total quality management, so that companies can achieve competitive advantage in facing the industrial revolution 4.0. Originality/value: This study adds moderating variables of technological innovation and knowledge management, which are thought to have a combined influence in the relationship of total quality management to competitive advantage which aims to answer the inconsistency of previous research findings. This study also uses the distribution of questionnaires to Bank Jatim employees, thus providing research results that are relevant to current conditions.